2013
DOI: 10.1007/s12263-013-0349-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype on the modulation of gene and protein expression by n-3 LC-PUFA in rats

Abstract: It is becoming increasingly apparent that responsiveness to dietary fat composition is heterogeneous and dependent on the genetic make-up of the individual. The aim of this study was to evidence a genotype-related differential effect of n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) on the modulation of hepatic genes involved in cholesterol metabolism. Fourteen spontaneously hypertensive (SH) rats, which present a naturally occurring variation in the gene encoding for sterol responsive element bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…PCSK9 has been shown to be regulated by SREBP-2, which communicates with hepatic proteins involved in cholesterol synthesis such as p-AMPK, AMPK and HMG-CoA reductase ( 23 ) . Previous preclinical studies have suggested that E 2 injection ( 4 , 24 ) or n -3 PUFA supplementation ( 11 , 25 ) reduce cholesterol synthesis by increasing AMPK phosphorylation, reducing expression of HMG-CoA reductase and reducing expression of SREBP-2 . Consistently, the present study shows that the reduced hepatic cholesterol synthesis was due to an up-regulation of p-AMPK and AMPK, an increase in the p-AMPK:AMPK ratio, and a down-regulation of HMG-CoA reductase and SREBP-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCSK9 has been shown to be regulated by SREBP-2, which communicates with hepatic proteins involved in cholesterol synthesis such as p-AMPK, AMPK and HMG-CoA reductase ( 23 ) . Previous preclinical studies have suggested that E 2 injection ( 4 , 24 ) or n -3 PUFA supplementation ( 11 , 25 ) reduce cholesterol synthesis by increasing AMPK phosphorylation, reducing expression of HMG-CoA reductase and reducing expression of SREBP-2 . Consistently, the present study shows that the reduced hepatic cholesterol synthesis was due to an up-regulation of p-AMPK and AMPK, an increase in the p-AMPK:AMPK ratio, and a down-regulation of HMG-CoA reductase and SREBP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike oestrogen, n -3 PUFA, EPA (20 : 5 n -3) and DHA (22 : 6 n -3) have been shown to decrease cholesterol by increasing hepatic bile acid synthesis by up-regulation of CYP7A1 , sterol 12 α -hydroxylase ( CYP8B1 ) and sterol 27-hydroxylase ( CYP27A1 ) ( 9 , 10 ) . In addition to increasing synthesis of bile acids, n -3 PUFA decrease blood levels of cholesterol by down-regulating SREBP-2 and HMG-CoA reductase and, thus, decreasing hepatic cholesterol synthesis ( 11 , 12 ) . However, the effect of n -3 PUFA on hepatic expression of PCSK9 has not been studied.…”
mentioning
confidence: 99%
“…High cholesterol intake in infancy may reduces endogenous cholesterol synthesis, probably by down-regulation of hepatic hydroxymethyl glutaryl coenzyme A (HMGCoA) reductase [ 45 , 46 ]. Additionally it has been showed that n -3 LCPUFA may modulate the HMGCoA reductase expression in rats [ 47 ]. This epigenetic mechanism, high cholesterol content in breast milk and down-regulation of HMGCoA reductase, might be further studied.…”
Section: Epigenetic Effects Of Human Breast Milkmentioning
confidence: 99%
“…Previous studies consistently observed that the supplementation of n-3 PUFA containing EPA and DHA significantly reduced blood concentrations of TG, TC, and LDL cholesterol in animals (Harris and Bulchandani 2006;Boschetti et al 2013) and humans (Ras et al 2014). The present study also showed that n-3 PUFA supplementation significantly and dose-dependently reduced serum and liver levels of lipids.…”
Section: Discussionmentioning
confidence: 76%